Prestigious recognition awaits best doctoral research - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (Universiti Putra Malaysia, 2014)
Innovation is a key driver of any economy in the world today, and universities play a fundamental role in strengthening the country’s innovation capability by promoting greater research.